PENGEMBANGAN E-BOOKLET MENGGUNAKAN APLIKASI HEYZINE UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI HAK DAN KEWAJIBAN - Rahayu Pratiwi Hegar Manah; Yuyun Elizabeth Patras; Mira Mirawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Rahayu Pratiwi Hegar Manah. 037121042. Developing an E-Booklet Using the Heyzine Application to Enhance Learning Outcomes on the Topic of Rights and Obligations. This research aims to develop an e-booklet to improve learning outcomes of fourth-grade students on the topic of Rights and Obligations at SDN Bantarkemang 2, to determine the feasibility of the developed media, and to test its effectiveness in the learning process. The research employed a Research and Development (R&D) approach using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 27 fourth-grade students at SDN Bantarkemang 2, Kota Bogor, during the even semester of the 2024/2025 academic year. Validation was conducted by three experts: a material expert, a language expert, and a media expert. The results showed that the e-booklet obtained a feasibility percentage of 97.1% from the material expert, 93.8% from the language expert, and 98.6% from the media expert, thus overall categorized as “Highly Feasible.” Effectiveness testing was conducted through pre-test and post-test assessments, which showed an increase in the average score from 81.11 to 97.40, with an N-Gain score of 0.90 categorized as high. Additionally, student response questionnaires indicated an average of 93%, and the teacher gave a perfect score of 100%. Based on all stages of development, it can be concluded that the e-booklet developed using the Heyzine application is highly feasible, effective, and appropriate to be used as a learning medium to improve student learning outcomes on the topic of Rights and Obligations in elementary school.